Anaesthetics of existence : essays on experience at the edge - Heyes, Cressida J. (Duke University Press, 2020)
"ANAESTHETICS OF EXISTENCE offers a phenomenological account of the limits of experience. Starting with a thought-provoking mishearing of Foucault's concept of "an aesthetics of experience"--That is, practices of the self that resist the will to knowledge--Heyes instead seeks to account for "anaesthetic experience," or that which cannot easily be considered experience, such as unconsciousness and substance-induced states. She explores how these liminal, and sometimes traumatic, physical experiences challenge our presumptions about how experience informs political subjectivity and agency. To do so, Heyes argues, allows us to consider the politics of embodied experience from a diverse set of realities. By deploying a phenomenological methodology that also takes into account the genealogy of the subject, she endeavors to move between two distinct registers: the lived experience of an individual and the individual's conditions of possibility, as well as the constraints on what we can be and do, and how we engage and exceed those constraints. Chapter 1 lays the groundwork for the book by examining the ways in which experience is mobilized for political ends. Agency is contingent on someone's ability to organize their experiences into a set of culturally significant and marketable categories; anaesthetic experiences, on the other hand, exceed those categories and are often depoliticized. The chapters that follow each dwell upon an anaesthetic experience to articulate a politics of experience. Chapter 2, for example, surveys media representations of sexual violence against unconscious women, showing that the circulation of these cases proliferates a violence of exposure against the survivors. Heyes argues that violence enacted upon a body that is "dead to the world" cannot be described as lived experience; yet it can shatter the victim's ability to reenter a shared intersubjectivity. Next, Heyes considers time spent under the influence of alcohol, everyday drugs, sedatives, and prescription drugs as a sensory response to a neoliberal prescription of time. While these anesthetic temporalities are constructed as a dangerous and irresponsible practice for people of color and poor people, wine brands like "MommyJuice" and "Mad Housewife" market anaesthetic substances to white upper-class women as a respectable way to exit from the demands of work and childcare. Finally, Heyes intertwines the difficulties of articulating the experience of childbirth with her own narrative of giving birth to her son, analyzing childbirth as a limit experience that is located at the breaking down of legibility and self-making, with everlasting effects on the body. ANAESTHETICS OF EXISTENCE will interest scholars working in feminist theory, phenomenology, and critical theory"--